Mental Health and Time Management Predict Academic Success in Part-Time Students: Kesehatan Mental dan Manajemen Waktu Memprediksi Keberhasilan Akademik pada Mahasiswa Paruh Waktu - Ikhwan, Rizky; Saputra, Praja Hadi; Kusumawati, Yulia Tri (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Part-time students often face significant challenges balancing academic and work responsibilities. Specific Background: These dual demands can result in psychological strain and limited time, both of which may negatively impact academic performance. Knowledge Gap: Despite growing concern over student well-being, few studies comprehensively assess how mental health and time management interact to influence academic outcomes in part-time populations. Aims: This study investigates the influence of mental health and time management on the academic performance of part-time Management students at Muhammadiyah University of East Kalimantan. Results: Using a quantitative survey of 110 students and multiple linear regression analysis, the study found that mental health (emotional exhaustion, social support, workload) and time management (planning, prioritization, time discipline, distraction control) significantly and simultaneously predict academic performance (grades, task completion, attendance, goal achievement). Novelty: This research integrates psychological and behavioral factors into a single model of academic success, emphasizing a holistic view of part-time student performance. Implications: Findings suggest that targeted institutional support for mental well-being and time management could enhance academic outcomes, guiding policy and student services toward more effective interventions. Highlights: Highlights the dual impact of mental health and time use on academic success. Uses quantitative data from 110 part-time students for analysis. Recommends institutional strategies to improve student outcomes. Keywords: Mental Health, Time Management, Academic Performance, Part-Time Students, Institutional Support